Swine T-Cells and Specific Antibodies Evoked by Peptide Dendrimers Displaying Different FMDV T-Cell Epitopes - de León, Patricia; Cañas-Arranz, Rodrigo; Defaus, Sira; Torres, Elisa; Forner, Mar; Bustos, María J.; Revilla, Concepción; Dominguez, Javier; Andreu, David; Blanco, Esther; Sobrino, Francisco (Frontiers in Immunology, 2021)
Dendrimeric peptide constructs based on a lysine core that comprises both B- and T-cell epitopes of foot-and-mouth disease virus (FMDV) have proven a successful strategy for the development of FMD vaccines. Specifically, B2T dendrimers displaying two copies of the major type O FMDV antigenic B-cell epitope located on the virus capsid [VP1 (140-158)], covalently linked to a heterotypic T-cell epitope from either non-structural protein 3A [3A (21-35)] or 3D [3D (56-70)], named B2T-3A and B2T-3D, respectively, elicit high levels of neutralizing antibodies (nAbs) and IFN-γ-producing cells in pigs. To assess whether the inclusion and orientation of T-3A and T-3D T-cell epitopes in a single molecule could modulate immunogenicity, dendrimers with T epitopes juxtaposed in both possible orientations, i.e., constructs B2TT-3A3D and B2TT-3D3A, were made and tested in pigs. Both dendrimers elicited high nAbs titers that broadly neutralized type O FMDVs, although B2TT-3D3A did not respond to boosting, and induced lower IgGs titers, in particular IgG2, than B2TT-3A3D. Pigs immunized with B2, a control dendrimer displaying two B-cell epitope copies and no T-cell epitope, gave no nABs, confirming T-3A and T-3D as T helper epitopes. The T-3D peptide was found to be an immunodominant, as it produced more IFN-γ expressing cells than T-3A in the in vitro recall assay. Besides, in pigs immunized with the different dendrimeric peptides, CD4+ T-cells were the major subset contributing to IFN-γ expression upon in vitro recall, and depletion of CD4+ cells from PBMCs abolished the production of this cytokine. Most CD4+IFN-γ+ cells showed a memory (CD4+2E3−) and a multifunctional phenotype, as they expressed both IFN-γ and TNF-α, suggesting that the peptides induced a potent Th1 pro-inflammatory response. Furthermore, not only the presence, but also the orientation of T-cell epitopes influenced the T-cell response, as B2TT-3D3A and B2 groups had fewer cells expressing both cytokines. These results help understand how B2T-type dendrimers triggers T-cell populations, highlighting their potential as next-generation FMD vaccines.